Not Indolamine 2, 3 Dioxygenase Polymorphisms, But Low Levels of IDO And IDO2 Are Associated with Behçet’s Syndrome - Uçar, Ülkü; Aydin Atalay, Yağmur; Özkaya, Güven; Oral, Haluk Barbaros (Medical principles and practice, 2025)
Objective: Behçet’s syndrome (BS) is a multisystemic disorder with a complex genetic background. Indoleamine 2,3-dioxygenase (IDO) and IDO2, key enzymes in tryptophan metabolism, have immunomodulatory effects. Specific IDO and IDO2 polymorphisms may influence enzymatic activity. This study aimed to explore the association between IDO/IDO2 gene polymorphisms and BS susceptibility, and assess serum levels of IDO and IDO2 in relation to BS. Subjects and Methods: Ninety patients with BS and 52 healthy controls were enrolled in this study. Predetermined single nucleotide polymorphisms (SNPs) were studied at specific gene loci for IDO and IDO2. Serum IDO and IDO2 levels were determined using ELISA. Results: No statistically significant differences were observed in the genotype and allele frequencies of IDO (rs7820268 and rs10108662) and IDO2 (rs4503083) between patients with BS and controls. Furthermore, no significant association was found between clinical findings and SNPs, except that the IDO rs7820268 CT genotype was significantly lower in patients with neurological involvement (0% vs 42%, p=0.026, OR=0.147, 95%CI=0.18-1.231). Serum levels of IDO and IDO2 were significantly lower in BS patients compared to controls (p<0.0000 and p<0.0001, respectively). Conclusion: Our research revealed that the serum IDO/IDO2 levels of BS were substantially lower than those in the control group. This finding has the potential to impact IDO activity and reduce immune tolerance. No correlation was observed between IDO/IDO2 polymorphisms and most clinical findings of BS. However, the IDO rs7820268 CT genotype was significantly reduced in neuro-Behçet’s syndrome, suggesting a protective effect. Larger prospective trials are needed to further explore these findings.